Antidiabetic Activity of Cocor Bebek Leaves (Kalanchoe pinnata Lam.Pers.) Ethanolic Extract from Various Areas - Dewiyanti, Indah Dwiatmi; Filailla, Euis; Megawati, Megawati; Yuliani, Tri (Journal of Tropical Life Science, 2012)
Antidiabetic activity of Cocor Bebek leaves (Kalanchoe pinnata Lam.Pers.) ethanolic extract from Bogor city, Kabupaten Bogor and south of Tangerang city has been studied. The study was conducted in vitro using glucosidase inhibitor method. The results of the study showed that IC50 of the extract from Bogor city, Kabupaten Bogor, and Tangerang Selatan city is 40.94 ppm, 33.58 ppm and 16.12 ppm respectively. Meanwhile, IC50 of quersetin which has antidiabetic activity is 10.22 ppm. The results showed that Cocor Bebek leaves (Kalanchoe pinnata Lam.Pers.) ethanolic extract had antidiabetic activity with IC50 less than 100 ppm. However, the activity is lesser than quercetin.Keywords:Kalanchoe pinnata Lam.Pers, antidiabetic activity, glucosidase inhibitor